2019
DOI: 10.3846/mbmst.2019.094
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a column shape cross-section on the punching capacity

Abstract: The article deals with non-linear modeling of slab-column connection which represents a fragment of flat slab supported by a column and loaded up to the punching shear failure. The aim of this parametrical study is the analysis of the length of reduced control perimeters in the case of columns with significantly elongated rectangular cross-section. The non-linear analysis was performed in program Atena and calibrated by test results obtained from the laboratory experiments carried out at Slovak University of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The aim of this paper is a numerical both linear and non-linear analysis of punching resistance around the edge of a wall with evaluation of the reliability of a simplified criterion for determining a reduced control perimeter. As it has been recently evaluated [9], the reduction of the control perimeter was not demonstrated even in the case of the columns with significantly elongated cross-section with ratio cmax / cmin = 7. In addition to that research, this analysis is made to find the real length of reduces control perimeter.…”
Section: Introductionmentioning
confidence: 83%
“…The aim of this paper is a numerical both linear and non-linear analysis of punching resistance around the edge of a wall with evaluation of the reliability of a simplified criterion for determining a reduced control perimeter. As it has been recently evaluated [9], the reduction of the control perimeter was not demonstrated even in the case of the columns with significantly elongated cross-section with ratio cmax / cmin = 7. In addition to that research, this analysis is made to find the real length of reduces control perimeter.…”
Section: Introductionmentioning
confidence: 83%
“…Several research teams dealt with non-linear analysis in Atena, including [6], who focused on the strengthening of flat slabs. According to the linear analysis, there is a partial decrease in shear forces at a distance of 1.5d from the support corners [4]. Figure 1 shows the decrease in shear forces of a specimen supported by a column with cross-sectional dimensions of 950 x 150 mm using different loading conditions.…”
Section: The Non-linear Analysismentioning
confidence: 99%
“…This research follows an analysis from 2019 [4], when, based on a nonlinear analysis in the Atena program, it was preliminarily concluded that in the case of uniform loading around the entire specimen, the length of the control perimeter is not reduced. In order to confront this statement, the specimen was further analyzed with a 0.15 m x 0.95 m column, which was subjected to a load test as well as a 3D nonlinear analysis in the Atena program.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear analysis was performed in the program Atena based on finite element method [5]. According to the linear analysis, there is a partial decrease in shear stresses at a distance of 1.5d from the support corners [4]. However, in the nonlinear analysis, the reduction of the control perimeter was not demonstrated despite the fact that the ratio of the longer column size to the effective depth was cmax / d > 3.…”
Section: The Non-linear Analysismentioning
confidence: 99%